False positive HIV diagnoses in resource limited settings: operational lessons learned for HIV programmes. - Leslie Shanks (PLoS ONE, 2013)
BACKGROUND: Access to HIV diagnosis is life-saving; however the use of rapid diagnostic tests in combination is vulnerable to wrongly diagnosing HIV infection when both screening tests give a false positive result. Misclassification of HIV patients can also occur due to poor quality control, administrative errors and lack of supervision and training of staff. Médecins Sans Frontières discovered in 2004 that HIV negative individuals were enrolled in some HIV programmes. This paper describes the result of an audit of three sites to review testing practices, implement improved testing algorithms and offer re-testing to clients enrolled in the HIV clinic. FINDINGS: In the Democratic Republic of Congo (DRC), Burundi and Ethiopia patients were identified for HIV retesting. In total, 44 false-positive patients were identified in HIV programmes in DRC, two in Burundi and seven in Ethiopia. Some of those identified had been abandoned by partners or started on anti-retroviral therapy or prophylaxis. Despite potential damage to programme reputations, no impact in terms of testing uptake occurred with mean monthly testing volumes stable after introduction of re-testing. In order to prevent the problem, training, supervision and quality control of testing procedures were strengthened. A simple and feasible confirmation test was added to the test algorithm. Prevalence of false positives after introducing the changes varied from zero percent (95% CI 0%-8.2%) to 10.3 percent (95% CI: 7.2%-14.1%) in Burundi and DRC respectively. CONCLUSION: False HIV diagnoses were found in a variety of programme settings and had devastating individual consequences. We re-tested individuals in our programmes while instituting improved testing procedures without a negative impact on test uptake. Considering the importance of correct diagnosis to the individual, as well as the resources needed to care for someone with HIV, it is critical to ensure that all patients registered in HIV programmes are accurately diagnosed.